Techno-economic analysis of solid oxide electrolysis using concentrated solar energy for green hydrogen production in South Africa. - Janse van Vuuren, Martin (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.